Gastrointestinal Symptoms and Irritable Bowel Syndrome Are Associated With Female Sex and Smoking in the General Population and With Unemployment in Men - Nilsson, Daniel; Ohlsson, Bodil (Frontiers in Medicine, 2021)
Background: The influence of daily life exposure on the gastrointestinal tract is not fully understood. This study aimed to examine associations between functional gastrointestinal symptoms and sociodemographic status and lifestyle habits in the general population. Methods: The Malmö Offspring Study (MOS) included 2,648 participants from the general population who had answered a questionnaire about sociodemographic status, lifestyle habits, medical health, and self-reported irritable bowel syndrome (IBS). The visual analog scale for IBS (VAS-IBS) was completed to assess gastrointestinal symptoms the past 2 weeks. Subjects with organic gastrointestinal diseases were excluded. Presence of self-reported IBS and gastrointestinal symptoms the past 2 weeks were used as dependent variables to study the associations with age, sex, body mass index, education, occupation, marital status, smoking, snuff using, alcohol drinking frequency, alcohol amount per drinking occasion, physical activity at work, and physical activity during leisure time, using logistic regression and generalized linear model. Results: Self-reported IBS was associated with gastrointestinal symptoms the past 2 weeks (p < 0.001). There was an association between IBS and female sex (p < 0.001), former smoking (p < 0.001), present smoking (p < 0.001), and an inverse association with drinking 3–4 standard glasses per occasion (p = 0.038). Gastrointestinal symptoms were associated with age 50–59 years (p = 0.009), ≥60 years (p = 0.004), female sex (p < 0.001), studying (p = 0.036), unemployment (p = 0.009), former smoking (p = 0.001), and present smoking (p = 0.012). In men, IBS was associated with middle-age and both IBS and gastrointestinal symptoms were associated with unemployment (p < 0.001 and p = 0.001, respectively). In women, IBS was associated with present smoking (p = 0.022), and gastrointestinal symptoms were associated with former smoking and inversely associated with higher age (p = 0.006) and intermediate physical activity at work (p = 0.008). No associations were found with BMI, education, marital status, or snuff using. Conclusion: Self-reported IBS in the general population shows strongest association with female sex and smoking, whereas gastrointestinal symptoms also are associated with unemployment and inversely associated with higher age. In men, both IBS and gastrointestinal symptoms are associated with unemployment. In women, both IBS and gastrointestinal symptoms are associated with smoking, whereas symptoms are inversely associated with higher age and intermediate physical activity.